2016
DOI: 10.11648/j.ajac.20160406.14
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antimicrobial Activity of Chloroform Extract of <i>Abutilon indicum</i>

Abstract: Powdered Abutilon indicum leaves were extracted from chloroform. Thin layer chromatography technique in combination with column chromatography was used to separate the chemically active constituents. The constituents were subjected to IR, NMR, EIMS analysis to identify the compounds contained in the extract. The antimicrobial activity of the plant extract was examined on Bacillus subtils, Klebsiella pneumonia, Pseudomonas aeruginosa, E.coli and the effect was compared with that of chloramphenicol. The comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Few transition metal complexes with Schiff base and studied their antimicrobial activities recently were reported [38]. It is also reported that certain metal-protein complexes of copper, magnesium, molybdenum, calcium, iron, zinc, chromium and vanadium are essential metallic elements and exhibit great biological activity, contributing in oxygen transport, electronic transfer reactions or the storage of ions, has generated massive attention in the study of systems containing these metals [41,43].…”
Section: Salicylidimines Are Very Important Example Of Photochromismmentioning
confidence: 99%
See 1 more Smart Citation
“…Few transition metal complexes with Schiff base and studied their antimicrobial activities recently were reported [38]. It is also reported that certain metal-protein complexes of copper, magnesium, molybdenum, calcium, iron, zinc, chromium and vanadium are essential metallic elements and exhibit great biological activity, contributing in oxygen transport, electronic transfer reactions or the storage of ions, has generated massive attention in the study of systems containing these metals [41,43].…”
Section: Salicylidimines Are Very Important Example Of Photochromismmentioning
confidence: 99%
“…The in-vitro evaluation of antimicrobial activities was performed according to the diffusion technique [13]. The bacteria were grown in nutrient broth at 37°C for 24 hours according to the previous literatures [41,42]. The complexes were tested using diffusion on solid media.…”
Section: Test For Antimicrobial Evaluationmentioning
confidence: 99%
“…A Northeastern Thai folk tradition recipe consisting Abutilon indicum and Mimosa pudica have been reported as being effective for diabetic treatment [18]. Furthermore, traditional medicinal use of A. indicum as antimicrobial [19], antidiarrheal [20], wound healing [21], antidiabetic/hypoglycemic & anti-obesity [22], anti-ulcer [22], and female fertility control [23]. Phytochemical investigation of A. indicum reported that alkaloids, amides, coumarins, benzoids, ionones, nucleosides, and steroids were isolated from its flowers, leaves, aerial parts, roots, and whole plants [11,[24][25][26][27][28][29][30].…”
mentioning
confidence: 99%